Experimentações em cultura, educação e cidadania: o caso da Associação Grãos de Luz e Griô - Silva, Juliana Lopes (2009)
The present work aimed to contribute for the discussions and reflections about social methodologies based on assays in education derived from new alternatives in culture. This study concentrated in providing a new convention of citizenship. The pedagogical and applied strategies of the Grão de Luz e Griô Association located in the city of Lençóis, at Chapada Diamantina, Bahia, Brazil, were analyzed. The evaluation also included the elaboration of a national project in collaboration with the Ministry of Culture considering the National Programo of Art, Education, Citizenship and Solidary Economy called 'Cultura Viva' (Alive Culture) and named 'Ação Griô' (Griô Action), inspired by its experience and methodology. This present proposal focused on integrating the communitarian knowledge from oral tradition in formal and non-formal educational practices for leading with children and young people by using Griô pedagogy as reference.